Biofilm Formed by Candida haemulonii Species Complex: Structural Analysis and Extracellular Matrix Composition - Ramos, Lívia S. (J Fungi (Basel), 2020)
Candida haemulonii species complex (C. haemulonii, C. duobushaemulonii, and C. haemulonii var. vulnera) has emerged as opportunistic, multidrug-resistant yeasts able to cause fungemia. Previously, we showed that C. haemulonii complex formed biofilm on polystyrene. Biofilm is a well-known virulence attribute of Candida spp. directly associated with drug resistance. In the present study, the architecture and the main extracellular matrix (ECM) components forming the biofilm over polystyrene were investigated in clinical isolates of the C. haemulonii complex. We also evaluated the ability of these fungi to form biofilm on catheters used in medical arena. The results revealed that all fungi formed biofilms on polystyrene after 48 h at 37 °C. Microscopic analyses demonstrated a dense network of yeasts forming the biofilm structure, with water channels and ECM. Regarding ECM, proteins and carbohydrates were the main components, followed by nucleic acids and sterols. Mature biofilms were also detected on late bladder (siliconized latex), nasoenteric (polyurethane), and nasogastric (polyvinyl chloride) catheters, with the biomasses being significantly greater than on polystyrene. Collectively, our results demonstrated the ability of the C. haemulonii species complex to form biofilm on different types of inert surfaces, which is an incontestable virulence attribute associated with devices-related candidemia in hospitalized individuals.